Novel Surface Marker for the Prospective Mesenchymal Stem Cell Characterization from Rabbit Visceral Adipose Tissue - Kuncorojakti, Suryo; Yudaniayanti, Ira Sari; Susanti, Lina; Susilawati, Helen; Aswin, Ahmad; Diyantoro, Diyantoro; Rodprasert, Watchareewan (Jurnal Medik Veteriner, 2025)
Rabbit as a laboratory animals play an important role in bridging basic research to clinical application. The exploration of rabbit mesenchymal stem cell (MSC) is still facing an obstacle regarding the standardization of characterization of MSC. This study is aimed to explore the novel candidate of rabbit MSC surface marker as an effort to establish the goal standardization of rabbit MSC. Three 2-month-old male White New Zealand rabbits weighing 2 kg were used as visceral rabbit adipose derived mesenchymal stem cell (Rab-ADMSC) donors. The cells were characterized according to their morphology characteristic, clonogenic and three-lineage differentiation capacity. Flow cytometry was used to evaluate the MSC surface markers of Rab-ADMSC against CD81, CD29, CD34 and CD45. The results of this study revealed that the Rab-ADMSC posses characteristic of MSC according to their morphology and differentiation capacity. It can be concluded that CD81 surface marker can be proposed as a stable alternative candidate marker for rabbit MSCs. This data is supported by other phenotypic characteristics of MSCs, both in morphology and in the ability of visceral Rab-ADMSCs to differentiate into adipogenic, osteogenic, and chondrogenic lineages.